A New Cytotoxic Pregnanone from Calotropis gigantea - Mao-Yuan Wang; Zhu-Nian Wang; Wen-Li Mei; Zhuang Han; Hao-Fu Dai (Molecules, 2008)
A new pregnanone, named calotropone (1), was isolated from the EtOH extract of the roots of Calotropis gigantea L. together with a known cardiac glycoside. The structures were elucidated by a study of their physical and spectral data. Compounds 1 and 2 displayed inhibitory effects towards chronic myelogenous leukemia K562 and human gastric cancer SGC-7901 cell lines.